Investigation of proper external air flow path for tubular fuel cell stacks with an anode support feature. (1st September 2018) - Chen, Daifen; Xu, Yu; Hu, Biao; Yan, Cheng; Lu, Liu
Graphical abstract: Highlights: Large scale 3D multiphysics model for tubular SOFC stack with anode support feature is developed. There is complex turbulent flow process within external air flow path of anode support T-SOFC stack. For 1in1out line external flow path most air flow are concentrated through the central zones of each tubes. For 2in2out U type external air flow path most air will flow along the margin zone of T-SOFC stack. An optimized external air flow path design for anode support T-SOFC stack is proposed and checked. Abstract: Although solid oxide fuel cell (SOFC) stacks are generally considered promising devices due to their many unique advantages, there are very few experiments and reports on anode support-type SOFC stacks with tubular (T-) designs, since it is quite difficult to determine a proper external air flow path design to support proper air and heat distribution qualities compared with cathode support T-SOFC stacks. In this paper, a large-scale 3D multiphysics model for the external air flow path of a convenient anode support T-SOFC stack is developed for the first time to investigate the general flow distribution characteristics of the external air flow paths. A novel external air flow path for an anode support T-stack is achieved by modifying the main and sub inlet/outlet manifolds, feed/exhaust headers structures and cross-section parameters. This new design is proven to greatly increase the air supply qualities among the tubes and over each tube surface and decrease the temperature gradients in the entire stack. The design could be the proper basic form used for anode support for T-SOFC stacks to achieve good stack performance and duration time in the near future.